PCR Results and PMTCT Treatment Outcomes among HIV-Exposed Infants in a Tertiary Hospital in Nigeria, 2010-2014 - Isaac Oludare Oluwayemi, MBBS, FWACP; Simeon Oladele Olatunya, MBBS, FMCP; Ezra Olatunde Ogundare, MBChB, FWACP (Global Health and Education Projects, Inc., 2015)
Background: Early infant diagnosis (EID) of human immunodeficiency virus (HIV) infection in pediatrics with the use of DNA polymerase chain reaction (PCR) is a way of assessing the retroviral status of HIV exposed infant with the view of early commencement of treatment for infected infants. It also serves as a way of assessing the effectiveness of prevention of mother-to-child transmission of HIV (PMTCT) in health care facilities. Methods: This was a 5-year prospective cross-sectional study at the Ekiti State University Teaching Hospital, (EkSUTH) Ado-Ekiti, Nigeria. Babies delivered to HIV-positive mothers who presented at EkSUTH between January 2010 and December 2014 were enrolled in the present study. PCR was done twice for all HIV-exposed infants. Statistical analysis was done using SPSS version 16.0. Results: One hundred and fifty eight infants were HIV exposed; 72 males and 86 females (M:F= 0.84:1). Eighty eight (55.7%) of the mothers had commenced highly active anti-retroviral therapy (HAART) before pregnancy, 56 (35.4%) during pregnancy, and 14 (8.9%) after delivery. Ten (6.3%) babies tested positive. Four (28.6%) of 14 exposed babies whose mothers commenced HAART after delivery tested positive to HIV compared to 3 (5.4%) of 56 babies whose mother commenced HAART during pregnancy and 3 (3.4%) of 88 babies whose mother commenced HAART before pregnancy. The difference was statistically significant (χ2 = 13.28, df = 4, p = 0.01). Conclusions and Global Health Implications: There is significant reduction in transmission of HIV from mothers to children with commencement of antiretroviral drugs before pregnancy in mothers and use of Nevirapine for all exposed babies for the first 6 weeks of life. Infants of HIV positive mothers can live healthy life free of HIV infection if their mothers participate in PMTCT program.